Expression of MX-1 and OAS-1 Genes in Peripheral Blood Mononuclear Cells during Early Pregnancy in Jersey Crossbred Heifers - Rahul, Girish; Sarath, Thulasiraman; Vijayarani, Kanagaraj; Arunmozhi, Narayanasamy; Pugazharasi, Chidambaram; Nag, Beladakere S. Pradeep (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The present investigation was conducted to study Myxovirus resistance (MX-1) gene expression and 2,5-Oligo-Adenylate Synthetase 1 (OAS-1) gene, present in peripheral blood mononuclear cells and its correlation with early pregnancy in heifers. A total of 24 Jersey crossbred heifers were selected and synchronized using TRIU-B®, PGF2α, and GnRH. All the experimental animals were fixed time inseminated, and blood samples were collected on days 0, 14, 15, 16, 17, 18, 19, 20, and 25 post-insemination. The animals were divided into two groups retrospectively 30-45 days later by pregnancy verification. Blood samples from six pregnant and six non-pregnant heifers were processed for expression studies of MX-1 and OAS-1 genes by real-time 2-ΔΔCT calculated PCR and their relative expression. The results showed that MX-1 mRNA levels were not different (p<0.05) until day 19 in pregnant heifers compared to non-pregnant heifers. The expression of OAS-1 gene was two-fold higher than MX-1, indicating that OAS-1 gene might be more specific to early pregnancy than MX-1.